Sinergi Motivasi dan Disiplin: Kunci Utama Peningkatan Kinerja Karyawan PT Rezeki Sejahtera - Angga Pratama; Umar Hanis; Saksono Budi (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to determine the effect of work motivation and work discipline on employee performance at PT Rezeki Sejahtera. The research methodology used is the Associative method. The population in this study were all employees at PT Rezeki Sejahtera, totaling 146 employees. By using the Slovin formula, a sample of 107 respondents was obtained. The data analysis method used multiple linear regression tests, correlation coefficients, determination coefficients, partial t tests and simultaneous F tests. The results of the study indicate that: (1) There is a positive and significant influence of Work Motivation on employee performance at PT Rezeki Sejahtera, this can be proven from the t-count value of 4.247> t-table 1.983 with a significance level of 0.000 <0.05. (2) There is a positive and significant influence of work discipline on employee performance at PT Rezeki Sejahtera, this can be proven from the t-count value of 4.885> t-table 1.983 with a significance level of 0.000 <0.05. (3) Simultaneously, there is a positive and significant influence of motivation and work discipline on employee performance at PT Rezeki Sejahtera. This can be proven by the equation of the calculated F value of 52.133 > Ftable 3.08 with a significance level of 0.000 < 0.05.